2009
DOI: 10.1007/s10800-008-9760-7
|View full text |Cite
|
Sign up to set email alerts
|

Bmim ionic liquids as media for the electrochemical oxidation of 2,6-di-t-butylphenol

Abstract: The electrochemical oxidation of the substituted phenol 2,6-di-t-butylphenol is studied at platinum electrodes using a number of 1-butyl-3-methylimidazolium (bmim) ionic liquids (BF 4 , PF 6 and N(CF 3 SO 2 ) 2 ), and compared with the oxidation obtained using a traditional solvent/electrolyte system (CH 3 OH/CH 2 Cl 2 and LiClO 4 ). The electrolysis leads to anodic coupling, resulting in the corresponding diphenoquinone, which upon reduction produces the biphenol. Best results were obtained for the convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…There have been several publications concerning with the electrooxidation of phenols in non-aqueous systems. The majority of substituted phenols form dimers as products of their electrooxidation typically the ones having one or more tert-butyl groups [1][2][3][4] and chlorophenols [5]. Previously, we found that some para-substituted phenol give reproducible current signal in acetonitrile on platinum electrode in 50 mM concentration [6].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several publications concerning with the electrooxidation of phenols in non-aqueous systems. The majority of substituted phenols form dimers as products of their electrooxidation typically the ones having one or more tert-butyl groups [1][2][3][4] and chlorophenols [5]. Previously, we found that some para-substituted phenol give reproducible current signal in acetonitrile on platinum electrode in 50 mM concentration [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids provide also an appropriate medium for electrooxidation processes due to their wide potential window. Some phenols showed reversible electrochemical behaviour using ionic liquids as solvent [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Although water is mainly in focus as solvent due to its practical interest (development of permselective layer, corrosion protection, wastewater treatment) but numerous electrochemical investigations are found in literature carried out in organic solvents. When phenol is electrochemically oxidized presenting itself in solution, an insulating poly(phenyleneoxide) film develops and some works utilized its properties [1][2][3][4][5][6][7]. However, polymers prepared from phenols are known as very weak electronic conductors, silylated poly(phenyleneoxides) have outgoing conductivity [8].…”
Section: Introductionmentioning
confidence: 99%